Case Report: Stroke Chameleon: Acute Large Vessel Occlusion in the Posterior Circulation With Paroxysmal Sympathetic Hyperactivity as the First Manifestation - Yin, Juntao; Wang, Wan; Wang, Yu; Li, Guofeng; Kong, Yongmei; Li, Xiaoqiang; Xu, Yingdong; Wei, Yuqing (Frontiers in Neuroscience, 2022)
Paroxysmal sympathetic hyperactivity (PSH) is a neurological emergency mostly secondary to traumatic brain injury (TBI). Acute large vessel occlusion (LVO) in the posterior circulation with PSH as the initial manifestation is uncommon. It may lead to catastrophic consequences for patients if not detected and treated timely. Here, we present three patients with acute LVO in the posterior circulation with PSH as the initial symptom. All patients were male and averaged 63 years old. The PSH Assessment Measure (PSH-AM) scores of all cases were > 17. Brain imaging showed that multiple lesions in posterior circulation were involved in three patients. Although the prognosis of all patients was poor, PSH symptoms disappeared in all patients after endovascular treatment. These cases suggests that acute posterior circulation-related ischemic stroke should be considered with PSH occurring as the first symptom. Extensive disconnection due to multiple lesions in posterior circulation may play an important role in the occurrence and development of PSH. Endovascular treatment may be effective for PSH caused by acute posterior circulation-related ischemic stroke. This is worthy of further study in the future.